2007
DOI: 10.1186/1471-2172-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Discriminators of mouse bladder response to intravesical Bacillus Calmette-Guerin (BCG)

Abstract: Background: Intravesical Bacillus Calmette-Guerin (BCG) is an effective treatment for bladder superficial carcinoma and it is being tested in interstitial cystitis patients, but its precise mechanism of action remains poorly understood. It is not clear whether BCG induces the release of a unique set of cytokines apart from its pro-inflammatory effects. Therefore, we quantified bladder inflammatory responses and alterations in urinary cytokine protein induced by intravesical BCG and compared the results to non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…Ten-to 12-wk-old C57BL/6 female and male mice (Jackson Laboratory, Bar Harbor, ME) were used in this research. Female mice were anesthetized, transurethrally catheterized as previously described (37), and instilled on days 1,7,14 (37) at a concentration of 1.35 mg to induce bladder inflammation was determined previously. Mice were studied 24 h after a single instillation (saline and BCG acute) or 7 days after 4 weekly instillations (saline chronic, control peptide chronic, PAR1-AP chronic, PAR2-AP chronic, and BCG chronic).…”
Section: Experimental Bladder Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten-to 12-wk-old C57BL/6 female and male mice (Jackson Laboratory, Bar Harbor, ME) were used in this research. Female mice were anesthetized, transurethrally catheterized as previously described (37), and instilled on days 1,7,14 (37) at a concentration of 1.35 mg to induce bladder inflammation was determined previously. Mice were studied 24 h after a single instillation (saline and BCG acute) or 7 days after 4 weekly instillations (saline chronic, control peptide chronic, PAR1-AP chronic, PAR2-AP chronic, and BCG chronic).…”
Section: Experimental Bladder Inflammationmentioning
confidence: 99%
“…Although the "usual suspects" vascular and lymphatic endothelial cells are the target of VEGF signaling in many normal and diseased tissues, expression of VEGF receptors by bladder cancer cells (15,33) suggested that the situation might be different or, at least, more complex in this organ. To answer this question experimentally, we chose to use two different stimuli that have been proven to induce significant and reproducible bladder inflammation and alter VEGF signaling upon intravesical instillation, namely protease-activated receptors activating peptides (PAR-APs) (39,41) and BCG (37).…”
mentioning
confidence: 99%
“…We instead established an orthotopic bladder tumor model in which the mouse bladder tumor cell line MB49 was implanted into the C57BL/6 mouse bladder. C57BL/6 mice were chosen, as they are widely used, permitting direct comparison with previously established clinical baselines (22). Following chemical injury and cell transplantation (19), tumor cell proliferation was observed, yet no tumor metastasis and miliary nodules were found in all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Intravesical instillation of BCG induces a complex inflammatory cascade in the bladder mucosa, reflecting activation of multiple types of immune cells and bladder tissue cells (Ratliff, 1991;Brandau and Suttmann, 2007;Alexandroff et al, 2010). Following BCG instillation, various leukocyte types infiltrate into the bladder wall including neutrophils, monocytes/macrophages, lymphocytes, NK cells and DC (Bohle et al, 1990a;Prescott et al, 1992;Saban et al, 2007). These infiltrating leukocytes, together with activated urothelial cells, produce numerous proinflammatory cytokines and chemokines.…”
Section: Il-10 In Bcg Treatment Of Bladder Cancermentioning
confidence: 99%
“…Subsequently, a transient massive amount of cytokines and chemokines (Bohle et al, 1990b;Boer et al, 1991a;De Reijke et al, 1996;Taniguchi et al, 1999;Saint et al, 2002;Nadler et al, 2003;Luo et al, 2007), together with a variety of leukocyte types (Boer et al, 1991a-c;Simons et al, 2008), can be detected in voided urine. The urine of mice treated with intravesical BCG also exhibits increased concentrations of cytokines and chemokines (Saban et al, 2007). In addition to local immune induction, intravesical BCG also results in systemic immune responses as manifested by increased levels of cytokines and chemokines in the serum (Elsasser-Beile et al, 2000;Magno et al, 2002).…”
Section: Il-10 In Bcg Treatment Of Bladder Cancermentioning
confidence: 99%